They planted the Cape : II (Historia, 2021)
When Van Goens sailed for St. Helena in the homeward-bound fleet on 10th May 1655 Van Riebeeck sent Verburgh in the "Tulp" with the fleet. He was to retrieve two horses and half-a-dozen saddles carried past the Cape, and to catch horses running wild, if he could, and some young pigs. Equally important were as many apple and orange saplings as the skipper could find room for. The gardener had told Van Ri'ebeeck that "hundreds of trees might be brought in tubs with the roots carefully covered with earth, and placed in the hold to be protected from salt spray." Meantime, V an Riebeeck applied himself with his customary industry to the expansion of the gardens. The ordinary kitchen-garden crops were already established, although legumes, necessarily staked well above ground, suffered from wind. The gardens now covered over 12 morgen, and he had bordered them with ditches 8 feet wide, and hedged them with wild thorn and a tall type of indigenous- tree, in order to provide shelter from the wind for the young fruit trees. Orchard trees and vines were to be the highlight of his endeavour from then onwards.
Keywords: Van Riebeeck; Van Goens; Farming; Gardens; Cape; Agriculture